Caring for older adults during the COVID pandemic and beyond: Experience from a specialized tertiary facility for the care of older persons in a low-resource setting. (2020)
The ongoing Coronavirus disease (COVID-19) pandemic has markedly changed health care provisions and arrangements for patient care. Older adults are most susceptible to worse outcomes. The public health impact of the disease in terms of morbidity and mortality has necessitated the evolution of management protocols for effective care of older persons. This review describes our experience during this period attending to the healthcare needs of both the acutely ill and clinically stable patients at the first purpose-built facility for the care of older persons in Nigeria, the Chief Tony Anenih Geriatric Centre (CTAGC), University College Hospital, Ibadan. A major strategy recommended by the World Health Organization was a lockdown with restricted movements and laid down rules for engagement. As such, the CTAGC also embarked on steps to ensure patient safety as well as effective care. Prior to the lockdown, targeted activities included fumigation of the centre as well as health education and promotional activities. Measures were put in place to care for up to 95% of our patients at home. Thus, a “Care in Place” approach was adopted to enable them to take ownership of their care. Ambulatory older patients were seen on an out-patient basis following scheduled appointments after a telephone consultation through the hospital’s designated lines. Clients were managed for their routine health conditions which were mostly non-communicable diseases (NCDs). Also,